Determinants of credit risk: evidence from commercial banks in Malaysia / Noor Hafizha Muhamad Yusuf ... [et al.] - Muhamad Yusuf, Noor Hafizha; Mohamad Shamsudin, Mohamad Shukery; Mohd Abdoh, Wan Mohd Yaseer; Badri Shah, Noor Sharida; Shekh Zain, Rozihanim (Universiti Teknologi MARA, Perlis, 2021)
The purpose of this study is to determine the relationship between microeconomic factors with credit risk among selected commercial banks in Malaysia. For this purpose, a sample of seven out of 27 commercial banks in Malaysia was selected and the microeconomic factors affecting credit risk with six measurements of return on asset (ROA), bank size, leverage, the ratio of capital, interest income and return on equity (ROE) were examined by applying Panel Regression Fixed Effect (FE) Model for a period 20 years from 1998 to 2017. The scope of the study covers seven selected commercial banks in Malaysia namely: Affin Bank Berhad, Alliance Bank Malaysia Berhad, CIMB Bank Berhad, Hong Leong Bank Berhad, Malayan Banking Berhad, Public Bank Berhad and RHB Bank Berhad. This study is using credit risk proxy by non-performing loan for dependent variable while independent variables that have been selected were Returned on Asset (ROA), bank size, leverage, Ratio of Capital, interest income and Return on Equity (ROE). The findings of the study managed to reject the null hypothesis for return on asset, bank size, leverage, interest income and return on equity which indicates the five microeconomic variables give a significant relationship with credit risk. There are positive relationships between leverage, interest income and return on equity with credit risk while return on asset, bank size and ratio of capital are negatively related to credit risk. However, the study fails to find any significant relationship between the ratio of capital and credit risk for commercial banks in Malaysia.